Mahabbah In The Perspective of Rabi'ah Al-Adawiyah and Ibn Taimiyah - Tasman, Alfadhli; Hadi, Mahfudz Syamsul (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2024)
This research focuses on the study of the concept of mahabbah (love according to sufism) according to Rabiah al-Adawiyah and Ibn Taimiyah. This research is an attempt to find out how the understanding of the thoughts, similarities and differences in the thoughts of the two figures in understanding mahabbah, especially mahabbah to Allah. Such as the meaning of mahabbah, types of mahabbah, object of mahabbah, and purpose of mahabbah. This research is library research, namely research conducted using data collection from various literatures. The approach used is historical-philosophical and the data collection method was carried out by the documentation method which was analyzed using the descriptive-comparative analysis method. The research data consists of primary data and secondary data. The results of the study show that mahabbah according to Rabiah al-Adawiyah is striped in a vertical direction, namely mahabbah which is only addressed to Allah SWT. regardless of other beings, rewards and punishments. Meanwhile, according to Ibn Taimiyah, mahabbah is striped in a horizontal direction, namely mahabbah which is addressed to Allah SWT. without having to turn his eyes to other beings, rewards and punishments. This is because mahabbah for creatures if it is based on Allah and cares about rewards and punishments is a manifestation of mahabbah for Allah. Although there are differences in the concept of mahabbah between the two, there are also similarities where both of them are of the view that only Allah SWT is the goal, because the one who has the right to receive mahabbah is the one who gives the sense of mahabbah itself. Thus mahabbah is only addressed to God. [Penelitian ini berfokus pada kajian konsep mahabbah (cinta menurut sufisme) menurut Rabiah al-Adawiyah dan Ibnu Taimiyah. Penelitian ini merupakan upaya untuk mengetahui bagaimana pemahaman pikiran, persamaan dan perbedaan pikiran kedua tokoh dalam memahami mahabbah, khususnya mahabbah kepada Allah. Seperti arti ma?abbah, jenis-jenis mahabbah, objek mahabbah, dan tujuan mahabbah. Penelitian ini merupakan penelitian kepustakaan, yaitu penelitian yang dilakukan dengan menggunakan pengumpulan data dari berbagai literatur. Pendekatan yang digunakan adalah historis-filosofis dan metode pengumpulan data dilakukan dengan metode dokumentasi yang dianalisis menggunakan metode deskriptif-komparatif. Data penelitian terdiri dari data primer dan data sekunder. Hasil penelitian menunjukkan bahwa mahabbah menurut Rabiah al-Adawiyah bergaris dalam arah vertikal, yaitu mahabbah yang hanya ditujukan kepada Allah SWT. terlepas dari makhluk lain, hadiah dan hukuman. Sementara itu, menurut Ibnu Taimiyah, mahabbah bergaris arah horizontal, yaitu mahabbah yang ditujukan kepada Allah SWT. tanpa harus mengalihkan pandangannya ke makhluk lain, hadiah dan hukuman. Hal ini dikarenakan mahabbah bagi makhluk, jika didasarkan pada Allah dan peduli dengan pahala dan hukuman adalah perwujudan mahabbah bagi Allah. Meskipun ada perbedaan konsep mahabbah antara keduanya, ada juga kesamaan dimana keduanya berpandangan bahwa hanya Allah SWT yang menjadi tujuannya, karena orang yang berhak menerima mahabbah adalah orang yang memberikan pengertian ma?abbah itu sendiri. Dengan demikian ma?abbah hanya ditujukan kepada Tuhan].